Macrozoobenthos as an indicator of habitat suitability for intertidal seagrass. (March 2023) - Gräfnings, Max L.E.; Govers, Laura L.; Heusinkveld, Jannes H.T.; Silliman, Brian R.; Smeele, Quirin; Valdez, Stephanie R.; van der Heide, Tjisse
Graphical abstract: Highlights: Macrozoobenthos data can be used to improve seagrass habitat suitability models. In the Wadden Sea, seagrass presence was reliably predicted with only four variables. Seagrass presence was negatively affected by higher Chl-a and ragworm biomass. Higher bivalve and mudsnail biomass increased the odds for seagrass presence. Abstract: Seagrass meadows form the foundation of many coastal ecosystems, but are rapidly declining on a global scale. To conserve and restore these key-ecosystems, improved understanding of drivers behind seagrass presence and recovery is needed. Many animals are known to both facilitate and inhibit seagrasses, but biotic factors are still rarely used as indicators of seagrass presence. Hence, we investigate if macrozoobenthos could be used as an indicator for intertidal seagrass ( Zostera marina and Zostera noltii ) habitat suitability in the international Wadden Sea. Additionally, we explore if macrozoobenthos can explain the differing seagrass recovery rates that have been observed between the Northern (Denmark and Schleswig Holstein) and Southern (Lower Saxony and Netherlands) regions of the Wadden Sea. To achieve this, we performed a Wadden Sea-wide survey at 36 intertidal locations, across three countries, and investigated the importance of 21 abiotic and biotic variables in explaining the presence and absence of intertidal seagrasses. Seagrass presence or absence could be reliably predicted (prediction error: 16.7%) with a multivariate logistic regression with only four variables; chlorophyll a, bivalve, ragworm and mudsnail biomass. We also found higher chlorophyll concentrations and ragworm biomass in the South compared to the Northern Wadden Sea, suggesting that eutrophication and associated community shifts might still inhibit seagrass recovery in the South. Our findings highlight the potential of using macrozoobenthos as indicators for seagrass habitat suitability. In areas, like the Dutch Wadden Sea, where macrozoobenthic surveys are common and where benthic data is readily available, our findings can be used to improve the understanding of seagrass recovery dynamics and the selection of suitable seagrass restoration sites.